Conservation of Non Wood Forest Resources for Sustainable Livelihoods - Bansal, Arun Kumar (Indian Forester, 2025)
Forest is a unique renewable natural local resource of global importance. India is one of the mega biodiversity countries of the world, and is home of 7.7% of world's bio-diversity. Non-wood forest products (NWFPs), also called Minor Forest Produce, although they are by no mean minor - are known to be source of livelihoods for over 300 million people living in and around forests and are in fact associated with their socio-economic and cultural lives. However, due to timber centric forest management, NWFPs have not got the importance they deserve. In recent years, the Non Wood Forest Resources (NWFRs) have gained importance due to their being vital source of livelihood for forest dependent communities and having a multiplier effect in the economy through employment generation in downstream value addition and trading activities. Multiplicity of Acts having a bearing on NWFRs has further compounded the prevalent confusion with regard to their ownership and management responsibilities. In this paper an attempt is made to analyze the legal framework impacting upon the NWFRs and the current status of their assessment and management, and suggest strategy for their conservation and management for sustainable livelihoods in India.